A promising Al-CeZrO4/HPW-incorporated SPEEK composite membrane with improved proton conductivity and chemical stability for PEM fuel cells. (April 2021) - Wang, Yingfeng; You, Jiabin; Cheng, Zhuowei; Jiang, Kun; Zhang, Linlin; Cai, Wanli; Liu, Yun-Quan; Li, Shuirong
An improved sulfonated poly (ether ether ketone) (SPEEK) nanocomposite membrane was prepared by incorporating both phosphotungstic acid (HPW) and Al doped cerium-based oxides (Al-CeZrO4 ) in SPEEK matrix. The HPW was immobilized by Al-CeZrO4 so that firmly dispersed acid–base pairs were formed. The introduction of Al-CeZrO4 helped improve the chemical stability of the pristine (baseline) SPEEK membrane without compromising the conductivity, and the addition of HPW further enhanced the conduction of protons through acid–base interactions. Stability tests showed that when the SPEEK/Al-CeZrO4 nanocomposite membrane was immersed in a Fenton's solution for 108 h at 80°C, a loss of 34.9% in proton conductivity was observed, which is 24.1% less than that of the pristine SPEEK membrane, indicating that the attenuation of membrane proton conductivity was inhibited. At the same time, the proton conductivity of the SPEEK/Al-CeZrO4 /HPW nanocomposite membrane (that has already incorporated HPW) was increased by 15.5% compared to the SPEEK/Al-CeZrO4 nanocomposite membrane. Hence, Al-CeZrO4 /HPW is considered as an effective inorganic nanofiller for improving both proton conductivity and chemical stability of SPEEK membranes, and the hybrid composite membrane is worth further studying.